Singular Space - Sevastjanov, Aleksandr (European Scientific Journal, ESJ, 2017)
Classical physics is a bastion of order and stability, but when creating physics of unstable systems, we are faced with selecting one of many possibilities and limited predictability at all levels of observation. This fact forces us to consider the concepts of instability and chaos in physics, and to describe them by means of singular space.